2012
DOI: 10.1097/fbp.0b013e3283512c85
|View full text |Cite
|
Sign up to set email alerts
|

The role of α1 and α5 subunit-containing GABAA receptors in motor impairment induced by benzodiazepines in rats

Abstract: Benzodiazepines negatively affect motor coordination and balance and produce myorelaxation. The aim of the present study was to examine the extent to which populations of GABAA receptors containing α1 and α5 subunit contribute to these motor-impairing effects in rats. We used the nonselective agonist diazepam and the α1-selective agonist zolpidem, as well as nonselective, α1- and α5-subunit-selective antagonists flumazenil, βCCt and XLi093, respectively. Ataxia and muscle relaxation were assessed by rotarod an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 32 publications
3
20
1
Order By: Relevance
“…Although not measured in this study, it is possible that the decreased distance traveled during the SRM task and decreased velocity during the SWM task are due to motor deficits produced by ZOL. This hypothesis is supported by previous studies that found prominent motor effects following ZOL administration (Depoortere et al, 1986;Steiner et al, 2011;Milic et al, 2012).…”
Section: Discussionsupporting
confidence: 79%
“…Although not measured in this study, it is possible that the decreased distance traveled during the SRM task and decreased velocity during the SWM task are due to motor deficits produced by ZOL. This hypothesis is supported by previous studies that found prominent motor effects following ZOL administration (Depoortere et al, 1986;Steiner et al, 2011;Milic et al, 2012).…”
Section: Discussionsupporting
confidence: 79%
“…Specific ligands binding to GABRA5 mediate muscle relaxation (Milic et al . 2012). Some of the identified transcriptional regulators have roles in myofibre type specification ( PRDM1 ) and fatty acid and glucose metabolism ( PRDM1 , MLXIPL , LIN28A ) (Wang et al .…”
Section: Resultsmentioning
confidence: 99%
“…Studies assessing the behavioral activity of diazepam in knock-in mice, which harbor single point-mutated receptors, have attributed the muscle relaxant actions of benzodiazepines to the α2/α3/α5-subtypes (Rudolph and Möhler, 2014). We have previously demonstrated that the α5-selective antagonist XLi-093 can significantly diminish the myorelaxant actions of diazepam in rats (Milić et al, 2012). Consistently, the first muscle relaxant effect of MP-III-022 was observed at a dose (10 mg/kg) postulated to elicit a selective strong potentiation of α5-GABA A receptors.…”
Section: Discussionmentioning
confidence: 99%